Analisa Karakter Iman Tomas Dalam Empat Teks Injil Yohanes Berdasarkan Teori Karakterisasi - Aryanto, Antonius Galih Arga Wiwin; Malino, Elvis (Forum, 2025)
Thomas is one of the disciples of Jesus who has a special role in the Gospel of John to convey the message of faith. There are four scenes in the Gospel of John that show the dynamic and developing character of Thomas' faith (11:16, 14:5, 20:24-29, 21:2). He is known for his initial doubting character and then the development of his faith culminates in his recognition of Jesus' personal identity, “My Lord and my God!”. This study will use text analysis with a narrative method that focuses on the character theory developed by Cornelis Bennema. The new contribution of this research paper is in the analysis of character, intrinsic and extrinsic motivation, character roles and character development of Thomas' following Christ. Thomas' confrontational experience with the other disciples and his demand for proof of Jesus' resurrection helped develop his character from a skeptic to a full believer